The 1884 uprising in Pangasinan unraveling its unknown ties with the Katipunan and the revolution - Marco, Sophia; Fernandez, Erwin S. (2015)
The short-lived 1884 uprising in Pangasinan is relatively obscure. No historian was able to link it with the Katipunan (KKK) and the revolution. Even Philippine history textbooks neither discuss nor mention this brief disturbance though it caused considerable alarm at that time. This essay looks into the connection of the Pangasinan uprising to the revolutionary organization and examines the parallelism of its causes, objectives, and aims with those of KKK. It provides a succinct account of the unrest and the investigation that followed its wake, which caught the attention of the propagandists since many intellectuals were arrested in suspicion of being part of the conspiracy.
Keywords: Pangasinan -- History -- Uprising, 1884; Philippines -- History -- Revolution, 1896-1898